English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Give it a go! i know ul love it

2006-12-03 05:34:29 · 5 answers · asked by Rob B 1 in Science & Mathematics Mathematics

5 answers

It's not that difficult:

2*ln(sec(x)) + tan(x) + C

email me for the steps

2006-12-03 05:44:46 · answer #1 · answered by Anonymous · 0 0

Permit my use of S for the elognated S in the integral.
Then,
S (1+tan x)^2 dx = S (1+2tan x + tan^2 x) dx
= S (sec^2 x + 2tan x) dx
= tan x + 2.ln |sec x| + c

where c is an arbitrary constant of integration.

2006-12-06 01:11:52 · answer #2 · answered by yasiru89 6 · 0 0

intergrate (1+tanx)^2
= (1+tanx)^3 / 3(secx)^2

2006-12-03 10:06:56 · answer #3 · answered by Kemmy 6 · 0 1

If you expand it out you get

int 1 + 2 tan(x) + tan^2(x) dx
int (1+tan^2(x)) + 2 tan(x) dx
int sec^2(x) + 2 tan(x) dx
= tan(x) - 2 ln|cos(x)| + C

where C is any constant.

2006-12-03 05:53:26 · answer #4 · answered by hij 2 · 0 0

int{(1+tanx)^2}dx
=int{tan^x+2tanx+1}dx[expand]
= -x+tanx-2ln(cosx)+x+C
=tanx-2*ln(cosx)+C

whereC=a constant

{from standard tables
int(tan^2(x)= -x+tanx)
int(tanx= -ln(cosx)}

i hope that this helps

2006-12-03 07:12:19 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers